The Relationship Between Cash Flow Management Practices and Perceived Business Performance : A Proposed Conceptual Model - Krishna Kumar, S.; Sivashanmugam, C.; Vennela, M. B. (Indian Journal of Finance, 2018)
The prime intention of this research paper was to create a conceptual framework to study the different dimensions of cash flow management practices and its linkages with cash flow forecasting practices and perceived business performance. The concepts of cash flow management, cash flow forecasting, and business performance made available the points to construct an integrated conceptual model, linking the aspects of cash flow management practices, cash flow forecasting practices, and perceived business performance. With the help of exhaustive literature review, it was found that variables relating to cash flow management practices were individually related to business performance. However, no model was found to investigate the combined influence of all the variables on business performance. Moreover, this paper proposed an indirect effect of CFM variables on business performance through cash flow forecasting practices, which is also a unique contribution of this paper. The four practices of CFM, (i.e., financing cash flow practices, operating cash flow practices, investment cash flow practices, and financial record keeping practices), cash flow forecasting, and perceived business performance were linked in a structured manner to examine their relationships. The current study will benefit the managers and owner managers in any enterprise to improve the business performance through cash flow forecasting practices and effective cash flow management practices.